2016
DOI: 10.1016/j.marpolbul.2015.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Identifying nitrogen sources to thermal tide pools in Kapoho, Hawai'i, U.S.A, using a multi-stable isotope approach

Abstract: Nitrogen (N) enrichment often results in coastal eutrophication, even in remote areas like Hawai'i. Therefore, determining N sources to coastal waters is important for their management. This study identified N sources to tide pools in Kapoho, Hawai'i, and determined their relative importance using three stable isotopes (δ(15)N, δ(18)O, δ(11)B). Surface waters and macroalgal tissues were collected along 100-m onshore-offshore transects in areas of high groundwater input for three months at low tide. Water sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In contrast, Waiʻōpae on the Eastern side received higher rainfall and groundwater influx and was defined by its complex underwater topography with partially submerged tide pools of different size and connectivity to the open ocean. Waiʻōpae was therefore subject to much higher fluctuations in temperature and salinity (Wiegner et al, ) than Kīholo, necessitating different short‐ and long‐term physiological responses. The magnitude of gene expression differences between sites was comparable to those in a similar study, which reported about 3,000 DEGs between two sites (Barfield et al, ) in Australian A. millepora .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Waiʻōpae on the Eastern side received higher rainfall and groundwater influx and was defined by its complex underwater topography with partially submerged tide pools of different size and connectivity to the open ocean. Waiʻōpae was therefore subject to much higher fluctuations in temperature and salinity (Wiegner et al, ) than Kīholo, necessitating different short‐ and long‐term physiological responses. The magnitude of gene expression differences between sites was comparable to those in a similar study, which reported about 3,000 DEGs between two sites (Barfield et al, ) in Australian A. millepora .…”
Section: Discussionmentioning
confidence: 99%
“…Waiʻōpae, while on an open coastline, was composed of numerous permanently and temporarily submerged basaltic tidepools, ranging in size and connectivity at low tide ( c. 1 m 3 to 2,500 m 3 , 0.25–3 m depth). Such complex underwater topography at Waiʻōpae, along with high rainfall and groundwater discharge, created high variability in temperature and salinity (Wiegner, Mokiao‐Lee, & Johnson, ).…”
Section: Methodsmentioning
confidence: 99%
“…• Data Set S1 Lapointe et al, 1999;Lapointe & Clark, 1992;Wiegner et al, 2016). However, there is limited data available describing temporal site-specific patterns of groundwater nutrient discharge and how these may have changed as a result of anthropogenic activity.…”
Section: 1029/2018gl078656mentioning
confidence: 99%
“…In many Pacific Island nations, rapid tourist and agricultural development, since the 1960s, has led to concerns over the contamination of coastal aquifers with anthropogenic nutrients (Knee & Paytan, ; Lapointe et al, ; Lapointe & Clark, ; Wiegner et al, ). However, there is limited data available describing temporal site‐specific patterns of groundwater nutrient discharge and how these may have changed as a result of anthropogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient concentrations also increase closer to shore. In another study of surface waters near these sampling sites, total dissolved nitrogen (TDN) ranged from 18 to 11 μmol L −1 from 0 to 100m from shore (Wiegner, Mokiao-Lee, & Johnson, 2016). Sites further from shore also have higher coral cover though corals are present near all sites.…”
Section: Introductionmentioning
confidence: 99%